2001
DOI: 10.3109/00207450109149756
|View full text |Cite
|
Sign up to set email alerts
|

Age Related Changes in Inhibitory Control as Measured by Stop Signal Task Performance

Abstract: A modified version of the stop signal task (suitable for use with very young children) was administered to a pre primary school group of children (<5 years, 6 months); a young primary group (5 years, 7 months to 7 years, 6 months); a mid primary group (7 years, 7 months to 9 years, 6 months) and a group of adults. Significant age differences in the ability to inhibit responding were found. These results highlight the need for measures of response inhibition which are appropriate for use with very young childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
76
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 19 publications
7
76
3
Order By: Relevance
“…Our current sample is between 6 and 10 years of age, one of the younger age groups tested with fMRI to date. Clearly, cognitive control continues to develop over this age range (Carver et al 2001;Casey et al 1997bCasey et al , 2001Diamond 1990;Diamond et al 1994;Diamond and Taylor 1996;Enns and Akhtar 1989;Enns and Cameron 1987;Enns et al 1998;Gerstadt et al 1994;Luria 1961;Passler et al 1985;Tipper et al 1989;Van der Meere and Stemerdink 1999), so the divergence in developmental trajectories between groups may just be beginning in our current sample. This may explain the lack of differences in overall accuracy for the children who participated in the imaging study.…”
Section: Discussionmentioning
confidence: 80%
“…Our current sample is between 6 and 10 years of age, one of the younger age groups tested with fMRI to date. Clearly, cognitive control continues to develop over this age range (Carver et al 2001;Casey et al 1997bCasey et al , 2001Diamond 1990;Diamond et al 1994;Diamond and Taylor 1996;Enns and Akhtar 1989;Enns and Cameron 1987;Enns et al 1998;Gerstadt et al 1994;Luria 1961;Passler et al 1985;Tipper et al 1989;Van der Meere and Stemerdink 1999), so the divergence in developmental trajectories between groups may just be beginning in our current sample. This may explain the lack of differences in overall accuracy for the children who participated in the imaging study.…”
Section: Discussionmentioning
confidence: 80%
“…The PFC exhibits differential activation in children and adults in numerous tasks addressing behavioral inhibition (Casey et al 1997b;Rubia et al 2000;Bunge et al 2002;Tamm et al 2002;Crone et al 2008), with both increased (Gravan et al 1999;Tamm et al 2002) and decreased (Casey et al 1997a;Marsh et al 2006) activations observed in children and adolescents compared to adults. Regulation of inappropriate thoughts and actions increases with age (Passler et al 1985;Harnishfeger and Bjorklund 1993;Carver et al 2001;Casey et al 2002Casey et al , 2005Galvan et al 2007;Yurgelun-Todd 2007), and the attainment of consistent inhibitory behavior has been linked Cold Spring Harbor Laboratory Press on May 10, 2018 -Published by learnmem.cshlp.org Downloaded from to maturation of the PFC (Neill 1976;Cardinal et al 2004;Andrzejewski et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Developmental changes in effortful control capabilities have been documented based on behavioral performance on cognitive tasks requiring executive control such as Stroop, flanker, and go/no-go tasks. Effortful behaviors attributed to the anterior attention system, such as the ability to inhibit prepotent responses, resist interference and detect and correct errors, increase steadily on such tasks from the toddler years through early adolescence (e.g., Carver, Livesey, & Charles, 2001;Casey et al, 1997;Diamond, 1990;Diamond & Taylor, 1996;Enns, Brodeur, & Trick, 1998;Gerstadt, Hong, & Diamond, 1994;Hooper, Luciana, Conklin, & Yarger, 2004;Jones, Rothbart, & Posner, 2003;Kochanska et al, 2000;Passler, Isaac, & Hynd, 1985;Rothbart et al, 2003). These behavioral findings are generally paralleled by neuroimaging findings showing that children activate the same cortical regions as adults while performing such tasks, however, the degree of activation tends to be inversely related to age.…”
Section: The Anterior Attention System and Effortful Controlmentioning
confidence: 99%